Wave propagation in rotating elastic solid - Erofeev, Vladimir Ivanovich; Kluyeva, Natalia Vladimirovna; Soldatov, Igor Nikolaevich (Computational Continuum Mechanics, 2008)
The propagation of bulk and surface waves in a rotating solid is studied. Analysis is carried out for a general case when the angle between the direction of wave propagation and rotation axis is arbitrary.